Pengaruh Kompensasi Langsung Dan Tidak Langsung Terhadap Semangat Kerja Pada CV. Indopura Jaya Enterprise - Rusmewahni; Nursaimatussaddiya (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2022)
Improving work performance, motivation, and job satisfaction of employees is through compensation. If compensation is given correctly, employees will be more satisfied and motivated to perform better in order to achieve organizational and personal goals. The purpose of this study was to determine the effect of direct and indirect compensation on morale at CV. Indopura Jaya Enterprise. To see and answer this research, the right method is needed, namely the multiple linear regression analysis method with simultaneous tests, partial tests and tests of the coefficient of determination. From this study it can be found: (1) Direct compensation variable (X1) and indirect compensation variable (X2), it is concluded that simultaneously or simultaneously have a positive effect on employee morale, while based on the F-Test the value of Fcount > Ftable is 7.984 > 4.1709 with a significant level of 0.002 or below 0.05. (2) The variable that most influences employee morale is the indirect compensation variable (X2), where the t-test obtains a significant value of 0.01 less than 0.05 and t count (3.740) > t table (2.042). (3) For the value of Adjusted R2 = 0.291. This means that the marketing department's employee morale is influenced by direct compensation and indirect compensation of 29.1%. While 70.9% is influenced by other variables not examined in this study, namely position, rank, financial security and others